Film Swapping in the Public Sphere: Youth Audiences and Alternative Cultural Publicities - Bolin, Göran (Javnost-The Public, 2000)
The article discusses questions concerning the cultural public sphere in relation to empirical material from a media ethnography of young men¹s use of extremely violent action and horror films on video, and how the young men's cultural practices, including media reception and film swapping, relates to their cultural production in the form of fanzines and amateur video films. The aim is to analyse this practice of film swapping, fanzine writing and amateur video making, in terms of cultural publicness, in order to shed light on those micro processes of communication that result in the formation of public spheres of various kinds. In the first part of the article some theoretical implications of the concepts cultural and political public spheres are discussed. Then follows a discussion on the internal communicative patterns within this alternative cultural public sphere, organised informally around fanzines and amateur video festivals. The dynamic relation between this alternative public sphere and other public formations, alternative as well as dominating or bourgeois, is then dealt with, and the different approaches among the various individuals is discussed. This is then followed by a discussion on the alternative cultural public.s relation to the market and state systems. Lastly, some general conclusions are drawn, covering the need to analytically separate cultural and political public spheres in order not to forget the task of the cultural public in mediating between market system and lifeworld, and thus not to dismiss the political implications of the cultural.